The Influence of Teaching Experience and Motivation on Teacher Performance in Learning at SMPN 18 Bandung - Yunia, Leni; Roswinna, Winna; Fitri Anggraeni, Annisa (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
In the world of education, the Covid-19 pandemic has made learning impossible to be carried out face-to-face, so the Ministry of Education and Culture in collaboration with the Ministry of Religion, the Ministry of Transportation and the Ministry of Health, has created an online learning policy (online). However, this is a very big and very difficult challenge, because Indonesia has a large area with thousands of islands spread from Sabang to Merauke, not all of which are accessible by today's technology. Based on the results of research and data analysis on teaching experience and motivation towards teacher performance that have been presented in Chapter IV previously, it can be concluded that teacher teaching experience has a percentage of questionnaire results of 84.43% which is categorized as good because it is in the interval of 80% - 90%. With the highest value on question item no. 5, namely being able to create heterogeneous groups because they know the level of student understanding. Meanwhile, what needs to be improved is the experience in creating learning media to help student understanding because it has the lowest value of 75%. The percentage of the influence of teacher teaching experience on teacher performance is less influential because the p value (0.644)> 0.05. Meanwhile, the level of teacher teaching motivation has a percentage of questionnaire results of 88.96% which is categorized as very good because it is in the interval of 81% - 90%.